Summary Record of Discussions of the National Development Council (NDC) Meetings Five Decades of Nation Building (Fifty NDC Meetings) Vol - II (15th To 25th Meetings) - Planning Commission (Planning Commission, 1960)
In considering the ways and means of maintaining reasonable stability of the price level it is essential to consider together all aspects of economic policy. The course of prices does not depend merely on the relation between demand and supply in respect of individual commodities; there are wider aspects to be considered such as fiscal policy, monetary policy, commercial policy, wage and profits policy, and—not the least important—the extent to which the Plan is well-balanced. It is not proposed in this note to go into all these aspects. It may be self-evident that some prices cannot but rise, partly because of insufficiency of supplies relatively to demand and partly because of tax measures. The aim should be to keep the prices of essential commodities from rising, even though other prices rise.
Government of India Planning Commission
Government of India Planning Commission